MODEL PENGGUNAAN SISTEM PEMBELAJARAN JARINGAN PADA MATA KULIAH KEOLAHRAGAAN DAN KEPRAMUKAAN SEKOLAH DASAR - Khairul Usman; Wesly Silalahi; Demmu Karo – Karo; Winara Winara (Universitas Negeri Medan, 2021)
Abstract: The purpose of this study is to produce a model of using online learning media in the Sport and Scouting Course of the Elementary School Teacher Education Study Program at the State University of Medan. The development of the concept of learning through online learning in courses can create technology sensitivity, both learning that increases the competence of physical and theoretical skills. The method that will be used is the research and development (R&D) method, which is an analysis that includes design, production, and evaluation. The study of development procedures used is the Richey and Klein level 4 method, namely carrying out research and development steps by designing products. The data obtained were then analyzed through the Forum Group Discussion (FGD). The results of]’ the study obtained that the effectiveness of the product was 93% with a very good category. The conclusion of the research is that the product can be used as a reference for the development model of lectures in the network at the State University of Medan. Keywords: Model, Learning, Course Abstrak: Tujuan penelitian ini adalah menghasilkan model penggunaan media pembelajaran dalam jaringan pada Mata Kuliah Keolahragaan dan Kepramukaan Program Studi Pendidikan Guru Sekolah Dasar di lingkungan Universitas Negeri Medan. Perkembangan konsep belajar melalui pembelajaran dalam jaringan pada mata kuliah dapat menciptakan budaya peka teknologi, baik perkuliahan berorientasi pada kompetensi keterampilan fisik maupun teoritis. Metode yang akan digunakan adalah metode research and development (R&D) bersifat analisis yang meliputi perancangan, produksi, dan evaluasi. Kajian prosedur pengembangan yang digunakan adalah metode Richey and Klein level 4 yaitu melaksanakan langkah-langkah penelitian dan pengembangan dengan merancangan produk. Data yang diperoleh kemudian dilakukan kegiatan analisis melalui Forum Group Discussion (FGD). Hasil penelitian diperoleh efektivitas produk 93% dengan kategori sangat baik. Kesimpulan penelitian adalah produk dapat dijadikan rule model pengembangan perkuliahan dalam jaringan di lingkungan Universitas Negeri Medan. Kata Kunci: Model, Pembelajaran, Mata Kuliah